Analisis Pengaruh Sektor Energi Terhadap Pertumbuhan Ekonomi Indonesia: Pendekatan FMOLS Periode 1993-2023 - Satriani, Jeanne Aleysia; Annis Nurfitriana Nihayah (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the impact of the energy sector on Indonesia’s economic growth, focusing on the variables of crude oil imports, crude oil exports, domestic oil consumption, and Brent crude oil prices. The research utilizes annual data for Indonesia from the period 1993–2023, sourced from the World Bank, Badan Pusat Statistik (BPS), and the International Energy Agency (IEA). The analytical method employed is Fully Modified Ordinary Least Squares (FMOLS), which is capable of addressing issues of endogeneity, autocorrelation, and non-stationarity in time series models. Long-term estimation results indicate that crude oil imports have a positive but statistically insignificant coefficient of 0.223292. Crude oil exports show a significant positive coefficient of 0.427778. Domestic oil consumption has a significant positive coefficient of 1.655629. Brent oil prices exhibit a significant positive coefficient of 0.028768. These findings suggest that, individually, crude oil exports and domestic oil consumption exert a significant and positive influence on GDP, indicating that these two variables are the main drivers of Indonesia’s economic growth from the energy sector. Conversely, crude oil imports and Brent oil prices, while positively associated, have statistically insignificant impacts suggesting that reliance on imports and global oil price fluctuations have not yet made a tangible contribution to GDP growth.